PERTUMBUHAN DAN HASIL TANAMAN SAWI (Brassica juncea L.) TERHADAP PEMUPUKAN ORGANIK DAN ANORGANIK - Kabilla Arsila Kurniawan; Army Dita Serdani; Palupi Puspitorini; Eko Wahyu Budiman (AGRORADIX : Jurnal Ilmu Pertanian, 2022)
The.aim of the research was to study the response of mustard plants to organic and inorganic fertilizers. The research was carried out in Kepanjenkidul Sub-district, using a Randomized Block Design Consisting of 7 treatments consisting of 3 replications. The treatments were : A = whithout fertilization (control) B = Dows inorganic fertilizer urea 2 g. C = inorganic fertilizer 1 g, C = inorganic fertilizer 1 g, D = organic fertilizer for goats 106 g, E = organic fertilizer for goat 212 g, F= organik fertilizer 106 g + inorganic 1 g and G = organic fertilizer 212 g + inorganic fertilizer 2 g. materials and tool used. Mustard seeds, urea fertilizer, goat manure, shovels, scales, polybags, stationery, and others. The variable that will be observed are plant heigh, number..of leaves, fresh weight mustard greens, all data taken at harvest. The data will be analyzed using analysis of variance. If there is a treatment effect, then the BNJ test is continued 5% level. The results showed that inorganic fertilizers had a significant effect on the growth and yield of mustard greens, while organic fertilizers had no significant effect on the growth and the yield of mustard greens. The higher the urea fertilizer, the higher mustard plant treatment.